Highly linear fundamental up‐converter in InP DHBT technology for W‐band applications. Issue 7 (11th March 2020) - Hossain, Maruf; Stoppel, Dimitri; Boppel, Sebastian; Heinrich, Wolfgang; Krozer, Viktor
Abstract: A fundamental up‐converter with high linearity is presented, realized as full Gilbert cell (GC) mixer using a 800 nm transferred substrate (TS) InP‐DHBT technology. The LO input of the Gilbert cell conducts from 75 to 100 GHz and requires 5 dBm of input power. The GC attains a single sideband (SSB) conversion gain of 10 ± 1 dB within the frequency from 82 to 95 GHz with a saturated output power of −1 dBm at 86 GHz and >5 dB conversion gain between 75 and 100 GHz. The up‐converter exhibits 25 GHz of IF bandwidth. The DC power consumption is only 51 mW.